FAKTOR – FAKTOR YANG MEMPENGARUHI MINAT MENGGUNAKAN UANG ELEKTRONIK BERDASARKAN MODEL UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) (Studi Pada Masyarakat Kota Malang) - Anis Rochmawati; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2021)
Every year the total issuer, electronic money, total transactions, and total electronic money infrastructure in Indonesia always increases. Recorded that until 2019 there were 38 electronic money issuing companies. From the potential users of electronic money in the community, there is a gap with the behavior of using electronic money. Therefore the focus in this research is the use of information technology with electronic money objects to adapt the UTAUT model to determine how much influence the performance expectations, business expectations, and social influences and conditions that facilitate the interest in using electronic money in the city of Malang. This research used a descriptive quantitative method. The `population of this research is all Malang city people with 115 samples and through a purposive sampling method. Data analysis through the Outer Model and Inner Model test stages in the Partial Least Square (PLS) analysis method. This study's results indicate that the variable performance expectations, business expectations, social influence, and behavioral interest have a positive effect on the interests of the people of Malang using electronic money. Benefits for stakeholders, especially governments & service providers, to always expand the Cooperation network with merchants so that the public can use electronic money in various places.Keywords : Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Behavioral Intention, Use Behaviour, Electronic Money.